2017
DOI: 10.1515/fv-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Elastic System Fibres in the Canine Prostate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Between more separated alveoli, the elastic fibres formed The elastic fibres in the mammary gland were seen to be much more dense than those observed in other exocrine glands [9,10,11] as was previously supposed. Elastic fibres form bridges between cells and their matrix [12].…”
Section: Elastinsupporting
confidence: 48%
“…Between more separated alveoli, the elastic fibres formed The elastic fibres in the mammary gland were seen to be much more dense than those observed in other exocrine glands [9,10,11] as was previously supposed. Elastic fibres form bridges between cells and their matrix [12].…”
Section: Elastinsupporting
confidence: 48%
“…We found a normal pattern [37] of elastic fibers in canine prostate (in the septa dividing the lobules, around the alveoli, ducts and the urethra). The interesting result was thatcanine PC, had a statistical higher median of elastin fibers (p=0.00229) than normal tissue.…”
Section: Discussionmentioning
confidence: 61%
“…An interesting finding was that solid canine PC had lower/absent Coll-IV expression than other PC patterns and normal tissues. Sinha et al, [37] found that Coll-IV immunostaining was less uniform or absent in the BM of poorly-differentiated human PC when compared to well-differentiated PC, HBP and normal human prostates. Similar results were also observed in feline and canine mammary tumors as well as in canine hemangiosarcoma [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…We found a normal pattern [51] of elastic fibers in canine prostate (in the septa dividing the lobules, around the alveoli, ducts and the urethra). The interesting result was that canine PC, had a statistical higher median of elastin fibers ( p = 0.00229) than normal tissue.…”
Section: Discussionmentioning
confidence: 99%